2017
DOI: 10.1172/jci83408
|View full text |Cite
|
Sign up to set email alerts
|

The chromatin remodeling factor CHD7 controls cerebellar development by regulating reelin expression

Abstract: The mechanisms underlying the neurodevelopmental deficits associated with CHARGE syndrome, which include cerebellar hypoplasia, developmental delay, coordination problems, and autistic features, have not been identified. CHARGE syndrome has been associated with mutations in the gene encoding the ATP-dependent chromatin remodeler CHD7. CHD7 is expressed in neural stem and progenitor cells, but its role in neurogenesis during brain development remains unknown. Here we have shown that deletion of Chd7 from cerebe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
70
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 77 publications
9
70
1
Order By: Relevance
“…The analysis of GCp‐specific Chd7 conditional mutant mice has identified important roles for CHD7 in regulating GCp apoptosis, proliferation and differentiation in the perinatal cerebellum (Feng et al, 2017; Whittaker et al, 2017). However, a reduction in GCp expansion is by itself not sufficient to explain the cerebellar foliation defects described here.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The analysis of GCp‐specific Chd7 conditional mutant mice has identified important roles for CHD7 in regulating GCp apoptosis, proliferation and differentiation in the perinatal cerebellum (Feng et al, 2017; Whittaker et al, 2017). However, a reduction in GCp expansion is by itself not sufficient to explain the cerebellar foliation defects described here.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in later stages of cerebellar development, En1/2 are essential for anterior‐posterior and medial‐lateral patterning of the cerebellum (Cheng et al, 2010; Joyner et al, 1991; Sgaier et al, 2007; Sillitoe et al, 2008; Sillitoe et al, 2010). Interestingly, our recent RNA‐seq analysis of Chd7 ‐deficient cerebellar GCps showed that En1 expression was upregulated in these cells, implicating CHD7 as a potential repressor of En1 expression (Whittaker et al, 2017). It is tempting to speculate that dysregulated En1 expression contributes to the specific foliation anomalies we have identified in Chd7 ‐deficient mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations